Incidence of Deep Vein Thrombosis in Hospitalized Chinese Medical Patients and the Impact of DVT Prophylaxis. (18th January 2011) - Cheng, Gregory; Chan, Crystal; Liu, Ying Ting; Choy, Yee Fun; Wong, Mei Mei; Yeung, Pui Kwan Ernest; Ng, Ka Ling; Tsang, Lai Shan; Wong, Raymond S. M.
Abstract : Objective . To evaluate the incidence of deep vein thrombosis in hospitalized Chinese medical patients and the impact of DVT prophylaxis. Methods . All cases of confirmed proximal DVT from 1 January 2005 to 31 December 2008 were reviewed retrospectively to determine the presence of risk factors and whether DVT developed: during hospitalization in medical wards or in case of readmission with a diagnosis of DVT within 14 days of discharge from a recent admission to medical wards. The impact of prophylaxis will be estimated by comparing the annual incidence of proximal DVT among medical patients hospitalized from 2005 to 2007 with that of 2008 (DVT prophylaxis commonly used). Results . From 1 January 2005 to 31 December 2008, 3938 Doppler ultrasound studies were performed for suspected DVT. Proximal DVT was diagnosed in 687 patients. The calculated incidence of proximal DVT among medical patients hospitalized for at least two days was1.8 %, 2 %, and1.7 % for the year 2005, 2006, and 2007, respectively. The incidence was1.1 % for 2008 (P < .001 ). Conclusion . Proximal DVT was substantial in Chinese medical patients, and DVT prophylaxis might reduce such risk.